2022
DOI: 10.3389/fphys.2022.848172
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Network Is Disrupted in Severe COVID-19

Abstract: The human body is a complex system maintained in homeostasis thanks to the interactions between multiple physiological regulation systems. When faced with physical or biological perturbations, this system must react by keeping a balance between adaptability and robustness. The SARS-COV-2 virus infection poses an immune system challenge that tests the organism’s homeostatic response. Notably, the elderly and men are particularly vulnerable to severe disease, poor outcomes, and death. Mexico seems to have more i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…It is important to note that when designating the RR channel, the largest mean absolute difference is observed for both T-SmvMDE and P-SmvMDE as well as the largest number of entries where the LS DisEn values are higher than the HS ones. This points towards a LoC process [10], [28] when moving from a steady state to a state that induces increased stress in the system, in alignment with the EP hypothesis [8], [29].…”
Section: Derivative Physiological Data Experimentsmentioning
confidence: 65%
See 2 more Smart Citations
“…It is important to note that when designating the RR channel, the largest mean absolute difference is observed for both T-SmvMDE and P-SmvMDE as well as the largest number of entries where the LS DisEn values are higher than the HS ones. This points towards a LoC process [10], [28] when moving from a steady state to a state that induces increased stress in the system, in alignment with the EP hypothesis [8], [29].…”
Section: Derivative Physiological Data Experimentsmentioning
confidence: 65%
“…Additionally, the mean absolute difference observed in each difference distribution and the number of entries that displayed an increased absolute value of difference during each SmvMDE configuration, compared to their mvMDE values, are reported. Finally, to highlight a potential directionality that could match the EP hypothesis [8], [29], the number of entries with a higher entropy value in the LS state than in the HS state are also reported for each configuration.…”
Section: F Derivative Physiological Data Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have indicated that female COVID-19 patients have an increased risk to develop long COVID [ 43 45 ], whereas male patients have higher odds of requiring intensive treatment unit (ITU) admission or of having a fatal outcome [ 46 ]. Previously, we have explained the distinct evolution of COVID-19 for both sexes in terms of differences in the structure of their corresponding physiological networks [ 40 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Females generally exhibit a better prognosis than males for acute systemic diseases such as COVID-19, attributed to their more robust physiological networks. 4 However, little is known about the impact of PASC, lowgrade inflammation 5 and sex differences on this systemic structure.Polymerised type I collagen (PTIC) is a potential drug for treating COVID-19 patients, proven to be effective against rheumatoid arthritis, 6,7 and is being investigated in multiple preclinical studies for other diseases.We analysed the data from a double-blind, randomised controlled trial of PTIC, [6][7][8][9] as an immune down-regulator, in COVID-19. We examined the dynamics of the physiological network, which characterises system-wide modifications during post-acute recovery.Between August 31 and November 7, 2020, 89 unvaccinated adult outpatients with Polymerase Chain Reaction (PCR)-confirmed COVID-19 were treated at the Instituto Nacional de Ciencias Médicas y Nutrición Salvador Zubirán.…”
mentioning
confidence: 99%